Perceived Facilitators and Barriers in Implementing Hospice Care: A Qualitative Study Among Health Care Providers in Binzhou, China - Heshuo Yu; Kate de Medeiros (SAGE Publishing, 2024)
Although many large Chinese cities have begun to implement hospice services, hospice care is still a relatively new concept in many parts of the country, especially in smaller cities. The purpose of this study was to gain a better understanding of health care providers' (physicians and nurses) perceptions of the facilitators and barriers to hospice care implementation in a fourth-tier city. Using a qualitative descriptive approach, semi-structured, open-ended interviews were conducted with 15 health care providers. Two major categories for developing hospice care were identified: (a) prospective facilitators and (b) perceived barriers. In addition, there is currently much ambiguity regarding what agency should oversee hospice services if implemented, who should be responsible for payment, the importance of developing interdisciplinary care teams and concerns about worker shortages. Future research is encouraged to investigate attitudes towards hospice care across various local healthcare systems and to promote the development of local hospice care support.